Unlike RNA-TBA (rTBA), iso-rTBA, the 2 `-5 `-linked RNA-thrombin-binding aptamer, is a functional equivalent of TBA - Wagh, Atish A. A.; Kumar, Vaijayanti A. A.; Ravindranathan, Sapna; Fernandes, Moneesha (Chemical Communications, 2023)
An antiparallel, functional RNA G-quadruplex of the 2 `-5 `-linked thrombin-binding aptamer (iso-rTBA) is reported for the first time. It can inhibit clotting and is remarkably stable to nuclease-degradation, besides having high thermal stability. It is thus, a superior candidate to TBA, rTBA or isoTBA, for further development as an anticoagulant.